CHILDREN OF THE REVOLUTION? A CASE STUDY OF THE MISSING NEXT GENERATION IN WOMEN'S POLITICAL WRITINGS IN THE NINETEENTH CENTURY AND HEDWIG DOHM'S NOVELS. (October 2014) - Mikus, Birgit; Woodford, Charlotte; Colvin, Sarah
ABSTRACT A recurring argument in political texts written by female authors in the second half of the nineteenth century is that women's emancipation and equal rights are a multi‐generational project. The so‐called '48ers were the first generation to fight for the most basic equal rights, and on this basis they argued that they would raise the next generation in the spirit of equality. These children of revolutionary parents would in their turn take up the fight for legal and social progress, so that, one step at a time, one generation at a time, full equality would be closer to being achieved. Over the course of the century, the generational argument was taken up by groups with different political interests and was adapted to reflect these. However, the same authors who called in their pamphlets for the passing‐on of democratic principles created female protagonists in their novels who are politically engaged in one form or another, but who do not have children. At the turn of the century, the author Hedwig Dohm published a trilogy of novels which appears to comment subliminally on the instrumentalisation of the idealised 'next generation' in political contexts. This article analyses the prevalence of the generational argument in several political texts written by women, and Dohm's retrospective evaluation of its feasibility in her trilogy, Schicksale einer Seele (1899), Sibilla Dalmar (1896), and Christa Ruland (1902).